Management of duodenal stump fistula following gastrectomy for gastric cancer: a systematic review (Journal of Surgical Sciences, 2020)
Introduction: Duodenal stump fistula (DSF) after gastrectomy has a low incidence but a high morbidity and mortality, and is therefore one of the most aggressive and feared complications of this procedure. This study was designed to assess the most effective treatment of duodenal stump fistula (DSF) after gastrectomy for gastric cancer.Methods: A systematic analysis of PubMed, MEDLINE, Current Contents, UpToDate databases, and the Cochrane Library Databases were carried out. A total of 80 manuscripts were retrieved and screened and nine studies published between 2009 and 2016 were selected. 241 cases of DSF were included in the study according to inclusion criteria. Only patients who underwent gastrectomy for gastric cancer were included in our review. Data about patient's characteristics, types of treatment, short and long-term outcomes were extracted and analyzed.Results: Three different approaches were applied: conservative (75 cases), surgical (138 cases) and percutaneous (59 cases). The overall mortality rate was 19% and significant complications were identified in 21% cases. Significant complications included sepsis, abscesses, peritonitis, bleeding, pneumonia and multiple organ failure. The conservative approach was reported in 5 studies including 75 patients who were clinically stable and complete resolution occurred in 92.3% of patients with a mean healing time of 35 days. Surgery was carried out if the patient was haemodynamically unstable or showed signs of sepsis. Overall outcome after surgery was poor with 31.1% mortality derived from six studies and in-hospital stay ranged from 1 to 1035 days (median 19). Percutaneous approach was often associated with conservative treatment and consisted of abscess drainage, biliary drainage or biliary diversion. The median healing time in this group was 42 days.Conclusion: Conservative approach is the first line of treatment in DSF, sometimes associated with percutaneous approach. Surgery should be reserved for severe cases or when conservative measures fail.Journal of Surgical Sciences (2018) Vol. 22 (1) : 62-66